2019
DOI: 10.1103/physrevb.100.214313
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of strongly interacting systems: From Fock-space fragmentation to many-body localization

Abstract: We study the t−V disordered spinless fermionic chain in the strong coupling regime, t/V → 0. Strong interactions highly hinder the dynamics of the model, fragmenting its Hilbert space into exponentially many blocks in system size. Macroscopically, these blocks can be characterized by the number of new degrees of freedom, which we refer to as movers. We focus on two limiting cases: blocks with only one mover and the ones with a finite density of movers. The former many-particle block can be exactly mapped to a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 104 publications
(189 reference statements)
2
79
0
Order By: Relevance
“…More generally, it would be interesting to investigate the role SLIOMs play in a many body localized phase, both at the boundary and in the bulk. In fact, recent works [36,93] investigated the MBL transition for models, which one could try to describe in the language of SLIOMs. It would also be interesting to look for other models exhibiting SLIOMs, either at their boundary or in their bulk.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, it would be interesting to investigate the role SLIOMs play in a many body localized phase, both at the boundary and in the bulk. In fact, recent works [36,93] investigated the MBL transition for models, which one could try to describe in the language of SLIOMs. It would also be interesting to look for other models exhibiting SLIOMs, either at their boundary or in their bulk.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, since the problem is fundamentally a many-body one, the underlying Fock space offers a seemingly natural framework within which to study and understand it [32][33][34][35][36][37][38][39][40][41][42][43]. More recently, it has been shown that this is indeed the case.…”
mentioning
confidence: 99%
“…More recently still, several models were found, where the many-body spectrum is sprinkled with highly athermal states that, by the nature of many-body spectra, live nearby in energy to thermal states in the middle of the spectrum [21][22][23][24][25][26][26][27][28][29][30][31][32][33][34][35][36][37]. These unusual states are called many-body scars.…”
Section: Introductionmentioning
confidence: 99%